Development of Potentiometric Phenol Sensors by Nata de Coco Membrane on Screen-Printed Carbon Electrode - Ani Mulyasuryani; Afifah Muhimmatul Mustaghfiroh (Journal of Analytical Methods in Chemistry)
Nata de coco, a bacterial cellulose as a result of coconut water fermentation, is a conductive polymer with a electrical conductivity of 553 μS/cm and has high mechanical stability. In this study, nata de coco was used as a supporting membrane for the development of phenol sensors in potentiometry. Nata de coco membrane containing phenol is coated on the surface of the printed carbon electrode (screen-printed carbon electrode). The cross-sectional area of the carbon electrode coated with the membrane is 1.5 × 3 mm2, while the reference electrode is Ag/AgCl. The thickness of the electrode membrane affects the Nernstian factor. The optimum Nernstian factor is produced by 100 μm membrane thickness containing 117.5 μg of phenol. Measurement of phenol solution was carried out at pH 11, in the concentration range of 10−8 to 10−2 mol/L, resulting in a Nernstian factor of 41.8 ± 1.3 mV/decade. The Nernstian factor increased to 55.7 ± 0.4 mV/decade if the membrane of the electrode contained 0.1% Fe3O4 nanoparticles. This sensor has been applied in the real sample of river water, resulting in good accuracy and precision.